75 EFFECT OF PSEUDOMONAS AERUGINOSA ON ALVEOLAR MACROPHAGES IN CYSTIC FIBROSIS. (1st March 2005) - Muhlebach, M. S.; Alexis, N.; Noah, T. L.
Abstract : Background: The main morbidity and mortality of cystic fibrosis (CF) are from chronic pulmonary infections with S. aureus and Pseudomonas aeruginosa (P. aer.), resulting in bronchiectasis and respiratory failure. Uncontrolled endobronchial inflammation contributes to development of bronchiectasis and may be involved in impaired bacterial clearance. The surface receptor CD14 is one of the principal molecules mediating LPS responses and HLA-DR is an MHC class II receptor involved in antigen presentation to lymphocytes. In preliminary studies comparing alveolar macrophages obtained by bronchoalveolar lavage (BAL) of CF and non-CF children, we observed decreased expression of both CD14 and HLA-DR. Aim: The aim of this study was to determine how S. aureus and P. aer. affect these surface receptors in vivo and ex vivo. Methods: CF and non-CF children undergoing clinically indicated bronchoscopy were asked to donate excess BAL fluid for this study. BAL cells were incubated in cell culture medium with or without bacterial supernatants and analyzed by flow-cytometry after staining for CD14 and HLA-DR. Intensity of surface marker expression (MFI) was compared between a) CF and non-CF subjects, and b) CF subjects with and without P. aer. infection. Results: Expression of both CD14 and HLA-DR was decreased in BALF macrophages in CF vs. non-CF disease control children (CD14: MFI 28 ± 5 vs. 53 ± 6, p<0.05; HLA-DR: 152 ± 37 vs. 397 ± 73, p<0.05). b) Within the CF group, subjects with P. aer. infection (n = 4) tended to have lower CD14 than non- P. aer. infected subjects (23 ± 9 vs. 31 ± 6). There was no difference in HLA-DR between P. aer. infected and uninfected subjects. c) Ex vivo incubation of BALF cells with supernatant of S. aureus (n = 14 different subjects) showed no effect on these surface markers. Incubation with P. aer. supernatant showed decreased CD14 and HLA-DR expression in BALF monocytes but not macrophages. This has been done in 4 subjects and has not reached statistical significance (CD14 control vs. P. aer.: 15.7 ± 4.8 vs. 2.3 ± 1.0 and HLA-DR 32.3 ± 12.6 vs. 4.0 ± 1.6). Conclusion: Expression of surface markers HLA-DR and CD14 on CF alveolar macrophages is decreased compared to non-CF conditions. P. aer. itself may contribute to this alteration as indicated by data from ex vivo experiments using P. aer. supernatants. We speculate that decreased expression of CD14 could decrease LPS-stimulated inflammatory responses in chronic infection. Impaired HLA-DR expression on lung macrophages and monocytes could result in a shift in T-lymphocytic response towards a Th2 type response. These changes could play a secondary role in the pathogenesis of CF lung disease.